Standardization of screening technique and evaluation of muskmelon genotypes for drought tolerance. Issue 1 (22nd July 2016) - Pandey, Sudhakar; Ansari, Waquar Akhter; Atri, Neelam; Singh, Bijendra; Gupta, Sunil; Bhat, Kangila Venkataraman
Abstract: A five-point drought stress screening methodology for muskmelon based on visual observation has been standardized by modifying an earlier field screening method. The scale (1 to 5), were categorized into five groups, namely, highly drought tolerant (1), drought tolerant (2), average drought tolerant (3), drought susceptible (4) and highly drought susceptible (5). To validate and standardized the technique, 48 genotypes of muskmelon were evaluated for two successive years. Important physiological parameters, i.e.: relative water content (RWC), electrolyte leakage, photosynthetic efficiency ( F v / F m ), chlorophyll concentration index (CCI), root and shoot length were measured and correlated to make screening results more reliable. Drought tolerance efficiency of genotypes was calculated based on yield, and drought-tolerant genotypes were identified with better yield efficiency and ranking on visual scale. Whereas, yield efficiency of some drought-tolerant genotypes were less, althouth they came under drought-tolerant scale. Being a tolerant genotype, these may not be economical for commercial cultivation. Under water-deficit condition a significant positive correlation was observed between drought tolerance efficiency, and RWC, F v / F m, CCI and root length. Out of 48 genotypes, 14 genotypes were came under highly drought-tolerant category based on 5 point scale.